Effectiveness of the Baby Friendly Community Initiative in Italy: a non-randomised controlled study. - Cattaneo, Adriano; Bettinelli, Maria Enrica; Chapin, Elise; Macaluso, Anna; Córdova do Espírito Santo, Lílian; Murante, Anna Maria; Montico, Marcella (BMJ Open, 2016)
OBJECTIVE: To assess the effectiveness of the Baby Friendly Community Initiative (BFCI) on exclusive breast feeding at 6 months. DESIGN: Controlled, non-randomised trial. SETTING: 18 Local Health Authorities in 9 regions of Italy. PARTICIPANTS: 5094 mother/infant dyads in 3 cohorts were followed up to 12 months after birth in 3 rounds of data collection: at baseline, after implementation of the intervention in the early intervention group and after implementation in the late intervention group. 689 (14%) dyads did not complete the study. INTERVENTION: Implementation of the 7 steps of the BFCI. MAIN OUTCOME MEASURES: The rate of exclusive breast feeding at 6 months was the primary outcome; breast feeding at discharge, 3 and 12 months was also measured. RESULTS: The crude rates of exclusive breast feeding at discharge, 3 and 6 months, and of any breast feeding at 6 and 12 months increased at each round of data collection after baseline in the early and late intervention groups. At the end of the project, 10% of infants were exclusively breast fed at 6 months and 38% were continuing to breast feed at 12 months. However, the comparison by adjusted rates and logistic regression failed to show statistically significant differences between groups and rounds of data collection in the intention-to-treat analysis, as well as when compliance with the intervention and training coverage was taken into account. CONCLUSIONS: The study failed to demonstrate an effect of the BFCI on the rates of breast feeding. This may be due, among other factors, to the time needed to observe an effect on breast feeding following this complex intervention.

Effect of Thalidomide on Clinical Remission in Children and Adolescents with Ulcerative Colitis Refractory to Other Immunosuppressives: Pilot Randomized Clinical Trial. - Lazzerini, Marzia; Martelossi, Stefano; Magazzù, Giuseppe; Pellegrino, Salvatore; Lucanto, Maria Cristina; Barabino, Arrigo; Calvi, Angela; Arrigo, Serena; Lionetti, Paolo; Lorusso, Monica; Mangiantini, Francesca; Fontana, Massimo; et al. (Inflamm Bowel Dis, 2015)
BACKGROUND: In a randomized controlled trial, thalidomide has shown to be effective in refractory Crohn's disease in children. This pilot study aimed at evaluating thalidomide in refractory pediatric ulcerative colitis (UC). METHODS: Double-blind, placebo-controlled randomized clinical trial on thalidomide 1.5 to 2.5 mg/kg/day in children with active UC despite multiple immunosuppressive treatments. In an open-label extension, nonresponders to placebo received thalidomide for an additional 8 weeks; all responders were followed up for a minimum of 52 weeks. RESULTS: Twenty-six children with refractory UC were randomized to thalidomide or placebo. Clinical remission at week 8 was achieved by significantly more children treated with thalidomide {10/12 (83.3%) versus 2/11 (18.8%); risk ratio, 4.5 (95% confidence interval [CI], 1.2-16.4); P = 0.005; number needed to treat, 1.5}. Of the nonresponders to placebo who were switched to thalidomide, 8 of 11 (72.7%) subsequently reached remission at week 8 (risk ratio, 4.0 [95% CI, 1.1-14.7]; number needed to treat, 2.45; P = 0.01). Clinical remission in the thalidomide group was 135.0 weeks (95% CI, 32-238), compared with 8.0 weeks (95% CI, 2.4-13.6) in the placebo group (P < 0.0001). Cumulative incidence of severe adverse events was 3.1 per 1000 patient-weeks. Peripheral neuropathy and amenorrhea were the most frequent adverse events. CONCLUSIONS: In this pilot randomized controlled trial on cases of UC refractory to immunosuppressive therapy, thalidomide compared with placebo resulted in improved clinical remission at 8 weeks of treatment and in longer term maintenance of remission. These findings require replication in larger clinical studies evaluating both thalidomide efficacy and safety.

Extra-large letter spacing improves reading in dyslexia. - Zorzi, Marco; Barbiero, Chiara; Facoetti, Andrea; Lonciari, Isabella; Carrozzi, Marco; Montico, Marcella; Bravar, Laura; George, Florence; Pech-Georgel, Catherine; Ziegler, Johannes C (Proc Natl Acad Sci U S A, 2012)
Although the causes of dyslexia are still debated, all researchers agree that the main challenge is to find ways that allow a child with dyslexia to read more words in less time, because reading more is undisputedly the most efficient intervention for dyslexia. Sophisticated training programs exist, but they typically target the component skills of reading, such as phonological awareness. After the component skills have improved, the main challenge remains (that is, reading deficits must be treated by reading more--a vicious circle for a dyslexic child). Here, we show that a simple manipulation of letter spacing substantially improved text reading performance on the fly (without any training) in a large, unselected sample of Italian and French dyslexic children. Extra-large letter spacing helps reading, because dyslexics are abnormally affected by crowding, a perceptual phenomenon with detrimental effects on letter recognition that is modulated by the spacing between letters. Extra-large letter spacing may help to break the vicious circle by rendering the reading material more easily accessible.
Keywords: Attention; Awareness; Child; Dyslexia; Form Perception; France; Humans; Italy; Language; Pattern Recognition, Visual; Phonetics; Reading; Vision, Ocular; Visual Fields